The backward season a wishing day novel - Myracle, Lauren 1969- (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2018)
"Now that her sisters Natasha and Darya have had their turn, Ava Blok finally gets her Wishing Day. But after seeing the unintended consequences of the wishes her sisters made, she's not sure what to wish for. The only thing she's certain of is that it's her job to set things right. Hopeful that she can put her broken family back together, and eager to prove her pessimistic older sisters wrong, Ava realizes that fixing the future means changing the past. Will the journey her wishes take her on end up costing her everything?" -- Publisher's annotation
Keywords: Fantastischer Roman; Magic / Juvenile fiction; Sisters / Juvenile fiction; Wishes / Juvenile fiction; Magic / Fiction; Dysfunctional families / Juvenile fiction; Wishes / Fiction; Sisters / Fiction; Time travel / Fiction; Time travel / Juvenile fiction; FAMILIES / Fiction; Magic; Sisters; Wishes; Juvenile works; Fiction; Fantasy fiction; Kinderbuch; Jugendbuch